2009
DOI: 10.1016/s0828-282x(09)70072-8
|View full text |Cite
|
Sign up to set email alerts
|

Familial unruptured sinus of Valsalva aneurysm obstructing the right ventricular outflow tract

Abstract: A neurysm of the coronary sinus of Valsalva (ASV) is rare. It may be congenital, sometimes in association with other cardiac defects (most commonly ventricular septal defect or coarctation), or it may be acquired. The first manifestation of ASV is most often related to rupture, whereas unruptured ASVs are rare. Although unruptured aneurysms are frequently asymptomatic without physical findings, they can be associated with complications and can compress adjacent structures. We present a case of a familial unrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The diagnosis of aneurysm of the sinus of Valsalva with RVOT obstruction was suspected only during a routine follow up echocardiography for the previous ALCAPA repair. There are multiple reports from the adult patient population describing aneurysm of sinus of Valsalva causing RVOT obstruction (8,9,11).As our case exemplifies, RVOT obstruction may be one of the manifestations of unruptured sinus of Valsalva aneurysm.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The diagnosis of aneurysm of the sinus of Valsalva with RVOT obstruction was suspected only during a routine follow up echocardiography for the previous ALCAPA repair. There are multiple reports from the adult patient population describing aneurysm of sinus of Valsalva causing RVOT obstruction (8,9,11).As our case exemplifies, RVOT obstruction may be one of the manifestations of unruptured sinus of Valsalva aneurysm.…”
Section: Discussionmentioning
confidence: 56%
“…The clinical manifestations of these aneurysms are related to their intrinsic mass effect on the adjacent cardiac structures. The clinical consequences of the mass effect in the nearby structures may be in the form of right ventricular outflow tract obstruction, heart block and coronary artery occlusion resulting in myocardial ischemia (4,(6)(7)(8)(9)(10)(11).In adults, unruptured sinus of Valsalva aneurysms may present with chest pain and dyspnea on exertion (8,9). Interestingly, Sundraum, et al from southern India, reported unruptured sinus of Valsalva aneurysm in a patient with inflammatory aortitis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Nishida et al [2] reported a case of a pulmonary valve endocarditis caused by the RVOT obstruction in association with aneurysm of the sinus of Valsalva. Aneurysm of the right sinus of Valsalva can protrude into the RVOT and cause obstruction [2][3][4]. The high-velocity jet created by the RVOT obstruction is usually responsible for the endothelial damage of the pulmonary valve and predisposes to infective endocarditis [2].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, the genetic predisposition of SVA is yet to be elucidated, as familial SVA is extremely rare. 5) Recently, an association with aortic aneurysm and SVA has been revealed in periventricular nodular heterotopia (PVNH) patients with loss-of-function Filamin A (FLNA) mutations, which were located on chromosome X and almost exclusively affect females. 6) Therefore, the present report reviewed an electronic case database of patients hospitalized for aortic surgery with aortic root diameter over 4.0 cm who have been referred for genetic testing in our institution.…”
mentioning
confidence: 99%